Beyond Ubiquity: Scale-dependent patterns of tardigrade diversity on the Iztaccíhuatl volcano - Alba Dueñas-Cedillo; Francisco Armendáriz-Toledano; Rodolfo J. Cancino-López; Jazmín García-Román; Enrico Alejandro Ruiz (PLoS ONE, 2026)
The diversity of tardigrade communities has been related with variables, such as habitat type, litter type, elevation, among others. However, the integration of variables in a multiscale context has been little explored, so this study analyzed tardigrade diversity and community composition across multiple ecological scales—moss substrates (rock, soil, bark), landscapes, and elevation zones—in a montane ecosystem. Mosses on tree bark harbor the highest species richness, including several substrate-specific taxa, while mosses on soil hosts unique species not found elsewhere. Mosses on rocks share species with soil mosses but lacks exclusive taxa. Among landscapes, the coniferous forests (mixed, Abies religiosa , and Pinus hartwegii ) exhibit high species richness and community similarity, with distinct local assemblages characterized by exclusive species within each forest type. Three generalist species were ubiquitous across all landscapes. Elevation analysis reveals maximal tardigrade richness and abundance in the alpine zone, with the nival zone supporting fewer species, mostly a subset of alpine taxa, and hosting a few unique species likely adapted to harsher conditions. Beta diversity analyses indicated that species turnover rather than nestedness predominantly drives community dissimilarities across substrates and habitats. These findings highlight the importance of considering scale-dependent patterns in understanding tardigrade distribution in complex montane environments.